Lactate and Bilirubin Index: A New Indicator to Predict Critically Ill Cirrhotic Patients’ Prognosis - Xiao-Fu Chen; Yuan Zhao; Wei-Zhen Chen; Xin-Tian Shao; Zhi-Ming Huang (Canadian Journal of Gastroenterology and Hepatology)
Objectives. We aimed to perform external validation of the prognostic value of the lactate and bilirubin (LB) index, a new indicator, and compare the ability of the LB index and other scoring systems to predict both short- and long-term mortality in critically ill cirrhotic patients. Materials and Methods. A number of 479 cirrhotic patients admitted into ICU were included in our research. We measured prognostic scores in the first 24 hours including LB index, Child–Pugh, SOFA, CLIF-SOFA, and MELD scores. The LB index was calculated as follows: ln [1000 × lactate (mmol/L) × bilirubin (µmol/L)]/2. The primary outcomes were 28-day and 3-year all-cause mortality. Multivariate logistic regression analyses were used to investigate the independent association between the LB index and the mortality in critically ill cirrhotic patients. The area under the receiver operating characteristic curve was used to assess the prediction accuracy of short- and long-term mortality of the clinical score. Calibration of the score was evaluated by Hosmer–Lemeshow goodness-of-fit test for significance. Results. Multivariate logistic regression analysis identified that the LB index (odds ratio: 5.487, 95% confidence interval: 3.542–8.501, P<0.001) was the strongest predictor for 28-day mortality. The LB index gave the highest area under the curve (0.791, 95% confidence interval: 0.747–0.836) in predicting 28-day mortality. For predicting 3-year mortality, the model for end-stage liver disease (MELD) score showed better discrimination ability with an area under the curve of 0.726 (95% confidence interval: 0.680–0.771). The risk of mortality significantly increased when the clinical scores were ≥ the optimal cutoff values. Conclusions. The LB index, a simple prognostic indicator, performs well in predicting critically ill cirrhotic patients’ short-term prognosis, while, for long-term prognosis, the MELD score is more appropriate.